Chemical composition of the atmospheric aerosols in arctic regions in the summer of 2021 - L. P. Golobokova; I. A. Kruglinsky; A. O. Pochufarov; I. I. Marinaite; N. A. Onishchuk; M. D. Kravchishina; M. V. Flint; M. Yu. Shikhovtsev; O. I. Khuriganova (Лëд и снег)
Atmospheric aerosol is an important characteristic of the state of the atmospheric air, therefore, in the summer of 2021, atmospheric aerosol samples were collected in the expeditions of the Shirshov Institute of Oceanology of the Russian Academy of Sciences to study the chemical composition (ions, trace elements, polyaromatic hydrocarbons) of aerosols in the Arctic atmosphere. The expeditions were carried out on the research ship (RS) Akademik Mstislav Keldysh in the Kara Sea (83rd cruise, June 18 - July 8, 2021), in the Barents Sea and the Norwegian-Greenland Basin (84th cruise, July 24 - August 26, 2021). It is established that the average total concentration of ions in the aerosol of the Kara Sea is 5.4±1.9 µg/m3, which corresponds to the average data obtained in previous years. In the aerosol of the Barents Sea and the Norwegian-Greenland basin, the average value of 5.0±2.1 μg/m3 was considered as potentially possible for the studied region. Concentrations of such ions as Na+, NH4 + and Cl-dominated in the aerosol composition of all regions. The average total concentration of trace elements in the composition of the aerosol of the Barents Sea and the Norwegian-Greenland basin is 1,5 times higher than in the aerosol of the Kara Sea. The predominant concentrations of trace elements in the aerosol of both study areas were Cr, Zn, Al, Fe. Mo, Sr, Ba, Mn, Sn, Ti, Pb, Cu, Ni. As a result of the calculation of the ranking of trace elements by atmospheric pollution in the aerosol of the Kara Sea, Fe, Cu, Ni, Pb are prioritized, and in the aerosol of the Barents Sea and the Norwegian-Greenland basin - Fe, Cu, Sn, Pb. The level of air pollution with trace elements in both areas is low. 13 compounds of polyaromatic hydrocarbons with an average total concentration of 0.65 ng/m3 in aerosol collected in 83 cruise, and 0.75 ng/m3 in 84 one were identified. Compounds of polyaromatic hydrocarbons with two and three benzene rings (naphthalene, phenanthrene and their homologues) coming from petrogenic sources accounted for 92 and 80% of the total amount of polyaromatic hydrocarbons, respectively. Atmospheric aerosol sampling for the study of chemical composition was carried out under conditions of fog of various densities, with precipitation and destruction of seasonal ice.